Beyond the Workshop: Results From a Longitudinal, Interprofessional Teaching Certificate Program - Ariel S Winn; Kathleen Huth; Alan M Leichtner; Lori R Newman (Journal of Medical Education and Curricular Development, 2023)
OBJECTIVES While most hospital-based, healthcare professionals are expected to teach and supervise, few receive training in education. We designed, implemented, and evaluated an interprofessional, hospital-based teaching certificate program based on experiential learning and reflective practice for healthcare professionals with little or no formal training in education. METHODS Participants attended educational seminars; incorporated new concepts, skills, and behaviors in their teaching; and submitted written reflections. Participants also met with an education coach, received feedback from a trained observer, and observed a “master teacher.” We used descriptive statistics to analyze a survey distributed to the 2017–2019 cohort. We also analyzed written reflections to determine whether participants described a new teaching skill, concept, or behavior, and how they applied these to their teaching. RESULTS Survey completion rate was 15/20 (75%). Participants described feeling connected to an educator community, establishing educational alliances with senior educators, and learning teaching strategies from other certificate members outside their own profession. Participants indicated they are more likely to pursue educational innovation, leadership, and scholarship. In the reflections, 88% described incorporating a new concept in their teaching. CONCLUSION Participants in an interprofessional teaching certificate program engaged in a curriculum of professional development in education. Graduates of the program reported knowledge gain, behavior change, and establishment of educational alliances and a community of practice.